Dietary fiber, lung function, and chronic obstructive pulmonary disease in the Atherosclerosis Risk in Communities (ARIC) Study - Kan, Haidong (2007)
Recent data suggest beneficial effects of fiber intake on chronic respiratory symptoms in adults that are independent of antioxidant vitamin intake, but little is known about fiber consumption in relation to lung function and chronic obstructive pulmonary disease (COPD). The authors investigated the association of fiber intake with lung function and COPD in 11,897 men and women from the Atherosclerosis Risk in Communities (ARIC) study. After controlling for potential confounders, positive associations between lung function and fiber intake from all sources as well as from cereal or fruit alone were found. Participants in the highest quintile of total fiber intake had 60.2 ml higher forced expiratory volume in 1 second (FEV(1)) (p for trend<0.001), 55.2 ml higher forced vital capacity (FVC) (p=0.001), 0.4% higher FEV(1)/FVC ratio (p=0.040), 1.8% higher percent predicted FEV(1) (p<0.001), and 1.4% higher percent predicted FVC (p=0.001), compared with those in the lowest quintile. The adjusted odds ratios of COPD for the highest versus lowest quintiles of intake were 0.85 (p=0.044) for total fiber, 0.83 (p=0.021) for cereal fiber, and 0.72 (p=0.005) for fruit fiber. This study provides the first evidence that dietary fiber is independently associated with better lung function and reduced prevalence of COPD.